2010
DOI: 10.1111/j.1365-2125.2010.03673.x
|View full text |Cite
|
Sign up to set email alerts
|

The ‘apparent clearance’ of free phenytoin in elderly vs. younger adults

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• The clearance of many drugs is reduced in the elderly, but the data regarding phenytoin are conflicting. Most studies have estimated phenytoin metabolic clearance using total drug concentrations (bound plus unbound), which may be confounded by protein binding effects. Free phenytoin concentrations are independent of protein binding and should more accurately reflect true metabolic clearance changes in elderly patients. WHAT THIS STUDY ADDS• The two studies reported in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…As a result, it is widely employed clinically (see examples [18][19][20]). An example of a typical steady-state PKPD model is given by: …”
Section: Steady-state Pkpdmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, it is widely employed clinically (see examples [18][19][20]). An example of a typical steady-state PKPD model is given by: …”
Section: Steady-state Pkpdmentioning
confidence: 99%
“…The steady-state condition provides a powerful framework from which to describe the magnitude of drug effect. As a result, it is widely employed clinically (see examples [18][19][20]). An example of a typical steady-state PKPD model is given by: In this setting, the assumption is made that the steadystate average concentration is sufficient to describe the important pharmacokinetic characteristics of the drug.…”
Section: Steady-state Pkpdmentioning
confidence: 99%
“…This is in contrast to previous studies which showed reduced phenytoin clearance in older individuals leading to higher plasma levels and toxicity. [26,27] We also found that males had 6 times higher odds of developing toxicity relative to females. Kesavan et al [20] did not find any association between gender and neurological toxicity as also by others.…”
Section: Discussionmentioning
confidence: 72%
“…An apparent clearance of free phenytoin tends to decrease in the elderly compared with younger people (53) . An apparent clearance of free phenytoin tends to decrease in the elderly compared with younger people (53) .…”
Section: Case Studymentioning
confidence: 97%